Design, synthesis and biological evaluation of a novel series of glycosylated platinum(iv) complexes as antitumor agents. Issue 25 (2nd June 2016) - Wang, Qingpeng; Huang, Zhonglv; Ma, Jing; Lu, Xiaolin; Zhang, Li; Wang, Xin; George Wang, Peng
Abstract : A new series of glycosylated Pt(iv ) complexes were designed, synthesized and evaluated for antitumor activities in vitro and in vivo . Abstract : A new series of glycosylated Pt(iv ) complexes were designed, synthesized and evaluated for antitumor activities in vitro and in vivo . The incorporation of glycosyl groups to the Pt(iv ) system has much influence on the antitumor abilities. Four lead compounds with activities comparable or even superior to cisplatin and oxaliplatin are screened out. These Pt(iv ) complexes could be reduced to release Pt(ii ) complexes and cause the death of tumour cells. The apoptosis-inducing properties of these compounds are similar to cisplatin. The accumulation of the glycosylated Pt(iv ) complexes in cells and DNA is higher than cisplatin and oxaliplatin. The in vivo assay demonstrates that the tested compounds inhibit the growth of HepG2 tumors with low toxicity.